Problems and Prospects of Community Policing An Analytical Study of India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The evolution of 'community policing' is of immense significance to the civilized society. The developments in the field of Community Policing have produced abundant literature in the form of both theoretical essays on the basic idea and practical accounts from on-going experiments. This study has examined various meaningful practices to upgrade the quality of police service through community policing projects. Material on a number of Community police initiatives taken within India has been accessed for this study. Also Community policing in countries like USA, Japan, Singapore, Hong Kong and U.K. etc. has been studied for understanding the basic frame worl< and its thrust areas. It has been observed that the Community Policing initiatives in India have gained momentum much after the same in USA, UK and Europe. Many initial initiatives in India lost glamour, not due to any defects in the scheme, but due to lack of clarity in the concept.